Impact assessment of interventions under Farmer FIRST Programme - Nikam, Vinayak; Kumar, Shiv; Jhajhria, Abimanyu; Kingsly, I. T.; Chahal, V. P. (Indian Farming, 2019)
The Farmers FIRST was initiated in 2016 and is one of the most ambitious projects of Indian Council of Agricultural Research (ICAR) aimed at participatory technology development, assemblage, assessment, refinement for location specific and need based technologies for the farmers to enhance their income and secure the livelihood. The Farmer FIRST Programme is developed as farmer in a centric role for research problem identification, prioritization and conduct of experiments and its management in farmer’s condition.